Managing work teams in exploratory projects (Dimensión Empresarial, 2020)
We propose a model aimed at enhancing the management of work teams in exploratory projects. An interdisciplinary approach was employed. Qualitative research methods were used to build and enhanced the model. Positive social interdependence, a construct from the Social and Educational Psychology fields, has the potential to meet the challenges presented by these projects. Results suggest that additional empirical field testing is needed to determine the validity of the model. From a pragmatic point of view, the application of the model’s prescriptions affords project managers additional tools to better deal with the inherent difficulties of exploratory projects.